2003
DOI: 10.1039/b208982c
|View full text |Cite
|
Sign up to set email alerts
|

Development of β-keto 1,3-dithianes as versatile intermediates for organic synthesis

Abstract: beta-Keto 1,3-dithianes can be generated by the double conjugate addition of dithiols to propargylic ketones, esters and aldehydes in excellent yields. As masked 1,3-dicarbonyl systems these substrates can be converted to a range of functionalised oxygen-containing heterocycles that can be used in natural product synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 15 publications
1
33
0
1
Order By: Relevance
“…As mentioned previously, Ley and coworkers have found that α,β-unsaturated alkynones generally undergo a double Michael addition and form 1,3-dithianes when treated with propane-1,3-dithiol under basic conditions [10]. Ketone 5, obtained in excellent yield by deketalization of 3,3,4,4-tetraethoxybutyne (Scheme 4), appears to be no exception to this rule and furnished 2-(3,3-diethoxy-2-oxopropyl)-1,3-dithiane (20) in excellent yield when reacted as outlined (Scheme 13).…”
Section: Chain Elongation Via a 2-substituted 13-dithianementioning
confidence: 68%
See 2 more Smart Citations
“…As mentioned previously, Ley and coworkers have found that α,β-unsaturated alkynones generally undergo a double Michael addition and form 1,3-dithianes when treated with propane-1,3-dithiol under basic conditions [10]. Ketone 5, obtained in excellent yield by deketalization of 3,3,4,4-tetraethoxybutyne (Scheme 4), appears to be no exception to this rule and furnished 2-(3,3-diethoxy-2-oxopropyl)-1,3-dithiane (20) in excellent yield when reacted as outlined (Scheme 13).…”
Section: Chain Elongation Via a 2-substituted 13-dithianementioning
confidence: 68%
“…Due to the reluctance of dithiane 22 to react even with aldehydes, it was decided to change strategy and follow a route involving protection of propargylic alcohols 8, deprotection of their ketal moiety to obtain the corresponding α,β-unsaturated alkynones, which were expected to undergo a double Michael addition and form 1,3-dithianes when treated with propane-1,3-dithiol under basic conditions [10]. As indicated by examples based on 4,4,5,5-tetraethoxypent-2-yn-1-ol (Scheme 14), this approach appeared to be successful provided the right protecting group was used.…”
Section: Modifications Via 13-dithianes From Substituted αβ-Unsaturmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] On the other hand, a convenient synthesis of dithioacetals from alkynes is quite limited. [5,6,7] As a general rule, the reaction of alkynes with thiols usually affords the corresponding vinyl sulfides in excellent yields. [8,9] Although monohydrosulfenylation proceeds smoothly, dihydrosulfenylation is only slightly promoted.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, different products are obtained from the reaction between activated alkynes and trivalent phosphorus nucleophiles in the presence of a proton source such as an alcohol or thiol [4]. The dithiol addition chemistry provides a useful general and versatile method to generate sulfur-containing compounds [5,6].…”
Section: Introductionmentioning
confidence: 99%